Pengaruh Penerimaan Pajak Dan Norma Subjektif Terhadap Kesadaran Wajib Pajak Yang Dimoderasi Preferensi Resiko - Ajeng Wijayanti; Martha Uliana Siahaan (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
The purpose of research is to place risk preference as a moderating variable on taxpayer revenue and subjective norm on taxpayer awareness. The research population is personal taxpayer. Data were collected by distributing questionnaries via google forms. The result show that tax revenues and risk preferences have a positive and significant effect on taxpayer awareness, while subjective norms have no effecton taxpayer awareness. Tax revenue have effect on taxpayer awareness moderater by risk preference, while subjective norms has no effect on taxpayer awareness moderated by risk preference